Factors in and Perspectives of Achieving Co‐Production of Knowledge With Arctic Indigenous Peoples - M. H. C. Rudolf; S. F. Trainor; J. O'Connor; E. Figus; R. Hum (Community Science)
Abstract Co‐production of knowledge (CPK) is a process of bringing together diverse perspectives from researchers, agency, and community partners to achieve a shared research goal. The main objective of this article is to provide tools for achieving CPK in research projects, especially with Alaska Native and Arctic Indigenous communities. Team members need to understand their positionality and be aware of assumptions and biases to come to jointly agreed upon project priorities. To assist researchers in reflecting on their positionality, we present research paradigm dispositions from commonly trained methodologies and academic norms. Differences across the dispositions are highlighted in decision‐making, success metrics, evaluation, and validation of outputs. Factors of Success were synthesized from existing literature on CPK, boundary spanning, the science of team science, convergence, Indigenous methodologies, and best practices to understand the CPK process. These Factors of Success are presented in a typical project life cycle logic model, categorized into inputs, process, and outcomes. Given the limited time and resources of research projects and activities, some factors will be given stronger emphasis over others. This article provides tools for transparent communication between researchers and community or agency partners.